Hukum Perburuhan Dan Ketenagakerjaan - Fani Rahmasaria; Romi Faslah (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
Employment law is the branch of law that deals with rules governing both individual and collective employment relationships. Also referred to as labor law. Employees that have a subordinate relationship with their employers are always the subject of this rule. This area of law deals with employment laws or agreements, the reciprocal rights and obligations between employers and employees, salary determination, job security, and workplace health and safety. In Indonesia, the employment phenomena happens frequently. Numerous events can occasionally result from this phenomena. Conflict and solutions are brought about by the occurrences that take place. But at the moment, there are more disputes than answers. Therefore, further regulations are required to reduce the likelihood of these events. Indonesia has taken this seriously by enacting Law No. 13 of 2003.